Avaliação dos processos de floculação em escala de bancada Jar test para tratamento convencional e com injeção de micro areia utilizando processamento digital de imagens - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Protection and adequate use of freshwater sources on planet must be searched exhaustively for the conservation of life on earth. Accelerated industrialization and demographic growth end up making the maintenance of hydric reserves, needed to guarantee the sustainable development, even more worrying. On the other hand, organizations with suitabletechnologies can stimulate the development of water treatment systems. In order to get the attention of those responsible for the operation of sanitation systems, cost and efficiency issues are paramount. This research focused on the compare, through Computational Vision technologies, the flakes formation process in Jar Test experiments applied on the basis of the water treatment for the conventional system and the system with Actiflo® technology. Actiflo® technology installed in the water treatment plant in Jardim Carvalho in PontaGrossa, consists of a compact system installed next to a conventional system, this system usesthe micro sand injection for flakes formation. The process is based in backed sedimentation,in which flakes structured by the combination between solid, coagulant and polymers are formed around of micro sand grains, increasing flakes weight which in turn, increase sedimentation velocity. This research demonstrates the effect of coagulation/flocculation processes on conventional application and with sand injection in the system, introducing the flocculant in different dosage and verifying the effect on flakes size and density. Verification is made through image processing in a computational program developed by the graduate program using the Matrix Laboratory – Matlab®, which uses a programming language and tools appropriate to the development of applications of technical nature. It was found in the conventional experiment a greater wingspan and a lower spatial density, reaching 259,4% of flakes in relation to the initial occupation. In the micro sand experiment, the density was greater but it was obtained a smaller average wingspan with higher average incidence of flakes of 3,47 flc/cm2 to 6,16 flc/cm2. The software successfully achieved its objectives, demonstrating the flocs individually in the jar and as a set, being able to compare the treatments in the parameters of characterization of the flocculation process.
Keywords: Floculação; decantação; modelagem física; micro areia; visão computacional; Flocculation; decantation; physical modeling; micro sand; computational vision; CNPQ::ENGENHARIAS::ENGENHARIA SANITARIA